2012
DOI: 10.1080/08109028.2012.676841
|View full text |Cite
|
Sign up to set email alerts
|

The governance of formal university–industry interactions: understanding the rationales for alternative models

Abstract: This article develops a conceptual framework to explain the economic rationales underpinning the choice of different modes of governance of formal university-industry interactions: personal contractual interactions, where the contract regulating the collaboration involves a firm and an individual academic researcher, and institutional interactions, where the relationship between the firm and the academic is mediated by the university. Although institutional interactions, for numerous reasons, have become more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…While faculty are not against technology transfer and other types of commercialisation of research results, they do tend to be rather guarded about attempts to promote the commercialisation of research (Martinelli et al, 2008). However, few studies have investigated researchers' reasons for involvement in commercialisation and collaboration with non-university actors (Lam, 2007;Bodas Freitas et al, 2012). A notable exception is Lee (2000), who, in a study of university-industry research collaboration, found that faculty collaborate with non-university actors for a variety of reasons, the most predominant of which include securing funds for research assistants and Ph.D. students, gaining insights into their own academic research, testing/applying theory, and supplementing funds for their own research (see also Duberly et al, 2007).…”
Section: Transferring Knowledge and Commercialising Researchmentioning
confidence: 99%
“…While faculty are not against technology transfer and other types of commercialisation of research results, they do tend to be rather guarded about attempts to promote the commercialisation of research (Martinelli et al, 2008). However, few studies have investigated researchers' reasons for involvement in commercialisation and collaboration with non-university actors (Lam, 2007;Bodas Freitas et al, 2012). A notable exception is Lee (2000), who, in a study of university-industry research collaboration, found that faculty collaborate with non-university actors for a variety of reasons, the most predominant of which include securing funds for research assistants and Ph.D. students, gaining insights into their own academic research, testing/applying theory, and supplementing funds for their own research (see also Duberly et al, 2007).…”
Section: Transferring Knowledge and Commercialising Researchmentioning
confidence: 99%
“…However, in emerging industry enterprises, continuous cooperation with universities after completion of projects is less common. This may have to do with the fact that students often act as mediators in these oneoff collaborations: the relationship of trust between the university and the company that collaborative projects require may not be possible on a single project basis [8]. Therefore, we began to think about what kind of university-enterprise cooperation can be regarded as authentic cooperation.…”
Section: Introductionmentioning
confidence: 99%